Obstetrics & gynaecology - Impey, Lawrence; Child, Tim (John Wiley & Sons Inc., 2017)
Obstetrics and Gynaecology by Impey and Child continues to be an invaluable and authoritative resource for healthcare and medical students. This comprehensive guide provides the perfect level of detail on history and examination, investigations and diagnosis, as well as common diseases, abnormalities, and complications in gynaecology and obstetrics.